KOORDINASI STAKEHOLDER DALAM RANGKA KERJASAMA PENEGAKAN HUKUM TERHADAP STABILITAS KEAMANAN PERAIRAN SELAT BANGKA - Hendrawan, Arry (Solusi, 2021)
Law enforcement and maintaining security in the maritime region of ​​Indonesia's national jurisdiction in accordance with the provisions of national law and international law are carried out in independent maritime security operations by the Navy and Maritime Security Operations in an integrated manner by the Navy along with other maritime agencies that have law enforcement authority in the region Indonesian national jurisdiction, namely the Maritime Security Agency, Directorate General of Sea Transportation and Directorate General of Immigration, Ministry of Law and Human Rights, Ministry of Marine Affairs and Fisheries, Indonesian Police, Customs, Ministry of Forestry, Ministry of National Education, Ministry of Environment, Directorate General of Oil and Gas, Ministry of Energy and Mineral Resources, Ministry Health and the National Narcotics Agency. The waters of the Bangka Strait are one of the quite dense national shipping traffic lanes, with the violations that occur in these waters, it is necessary to coordinate with other stakeholders in the framework of law enforcement cooperation in order to maintain the stability of the security of the waters of the Bangka Strait. The purpose of this study is to analyze the effect of coordination with other stakeholders in the framework of law enforcement cooperation on the stability of the waters of the Bangka Strait. The method used in this research is quantitative method. The result of the research reveals the significant influence of coordination with other stakeholders in the framework of law enforcement cooperation on the stability of the waters of the Bangka Strait.